Ductal carcinoma in situ (DCIS) presenting as a cystic retroareolar lesion in an African American man. Issue 6 (4th May 2021) - Ndumele, Amara; Kerger, Amy; Tozbikian, Gary; Obeng‐Gyasi, Samilia; Oppong, Bridget A.
Abstract: Ductal carcinoma in situ (DCIS) in males is rare, and there are limited data aimed at understanding the adequate workup, imaging, and follow‐up for men who present with breast masses. Attention should be given to black men who have a higher cancer risk and worse prognosis than white male counterparts. Abstract : Ductal carcinoma in situ (DCIS) in males is rare, and there are limited data aimed at understanding the adequate workup, imaging, and follow‐up for men who present with breast masses. Attention should be given to black men who have a higher cancer risk and worse prognosis than white male counterparts.